Perkembangan Fasies Sedimen Formasi Mamberamo Berumur Miosen Akhir-Pliosen di Cekungan Papua Utara - Mamengko, David Victor; B.Sendjadja, Yoga; Mulyana, Budi; Panggabean, Hermes; Haryanto, Iyan; Lelono, Eko Budi; Musu, Juwita Trivianty; Panuju, Panuju (Jurnal Geologi dan Sumberdaya Mineral, 2019)
North Papua Basin is a fore arc basin located in northern coastal of Papua Island. This basin filled by Middle-Upper Miocene turbidite sediment and overlied by Upper Miocene – Quarternary clastic sediment. Upper Miocene – Quaternary clastic sediments (Mamberamo Formation) composed by interbedding conglomerate, sandstone and shale as molasses deposit. A detailed stratigraphic study was performed to identify facies and its association of the Mamberamo Formation to that give a new perspective on the characteristics and development of facies succession of Lower Mamberamo Formation. Result  shows that the Lower Mamberamo Formation consists of three facies: A) cross bedding sandstone (subtidal), B) heterolothic silty shale (intra-tidal), C) carbonaceous shale (supra-tidal) deposited on Late Miocen to Plio-Pleistocene during centra range orogeny (syn-orogeny) as molasses deposits.Keywords: Fore arc basin, North Papua Basin, Mamberamo Formation, molasse deposits.